O mundo do trabalho e a formação profissional: a dificil adequação - Martino, Mariluci Alves (2001)
The present social, political and economical transformations show the transition period we have been facing. With the changes of management paradigms, knowledge becomes a key element of social transformation. Professional schools, just like corporations, are having to change their organizational structures, so that they can face the new demands. This means serious challenges for the education system, since the new trends modify both professional practice and the type of education schools have to offer. In this study, we will first see how jobs are being transformed, and the way corporations are facing these changes. We will then discuss the concept of qualification. After that, as an example of the difficulties teaching institutions face in order to be respond to the new demands, we will present a brief history of the professional education system in Brazil and of the Centro Paula Souza. Finally, we will present an experience of partnership between CEETEPS and the transport companies. This structure will allow us to show how three key trends, namely how jobs are changing, how the corporations are facing these changes, and how professional training institutions are responding, can actually be faced by partnership and more flexible management